Українські ментальні архетипи у творчості Станіслава Людкевича (деякі штрихи до трактування кантати-симфонії «Кавказ») - Кашаюк, Вікторія Миколаївна (My University, 2020)
The reflection of Ukrainian mental archetypes in the works by Stanislav Liudkevych on the example of cantata-symphony «Caucasus» is analyzed in the article. For this purpose, a preliminary review of the Ukrainian mentality phenomenon is carried out. According to the author, it is based on two main elements, which are cordo- and volitional. As a result, it is stated that the spiritual-religious idea, which is the key to T. Shevchenko’s philosophy, was interpreted by S. Liudkevych in the spirit-willed version. This is the reason to see in the cantata-symphony the creation of a new «Caucasus» concept.
Keywords: українські ментальні архетипи; кордоцентризм; творчість С. Людкевича; творчість Т. Шевченка; 78.27